Influence of materials and machining parameters on WEDM of Al/AlCoCrFeNiMo0.5 MMC. Issue 7 (19th May 2019) - Karthik, S.; Prakash, K. Soorya; Gopal, P.M.; Jothi, Sathiskumar
ABSTRACT: The current study intends to optimize the wire electric discharge machining (WEDM) parameters while machining the newer AlCoCrFeNiMo0.5 high entropy alloy (HEA) particles-reinforced aluminum composites. AlCoCrFeNiMo0.5 HEA particles produced through arc melting technique are reinforced here for different weight % (0%, 3%, 6%, 9%, 12%, and 15%) along with pure aluminum by the way of powder metallurgy. WEDM studies were conducted by varying the appropriate parameters, namely, pulse ON time, pulse OFF time, and wire feed. Based on the selected parameters, through Taguchi method L18 orthogonal array is designed; the optimal parameter combination for better surface finish, material removal rate (MRR), and reduced kerf width (KW) is identified. For better understanding, through ANOVA, also the effect of each input variables over these adopted response variables was analyzed. The yielded results reveal that addition of AlCoCrFeNiMo0.5 HEA as reinforcement has considerable effect over the response variablessuch that MRR and KW reduces; surface roughness increases with increase in HEA %. ANOVA results confirm that pulse ON time has higher effect over the response variables than any other parameters involved for the study. Multi-objective optimization done through Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) methodology answers that MRR and surface finish have improved, whereas KW gets reduced noticeably.